Factors associated with the perception of inadequate sanitary control in 12 Latin American countries during the COVID-19 pandemic - Mejia, Christian R.; Liendo-Venegas, Daniela; García-Gamboa, Fernanda; Mejía-Rodríguez, Miguel A.; Valladares-Garrido, Mario J. (Frontiers in Public Health, 2022)
Introduction: Sanitary control mechanisms differ greatly from country to country. Therefore, it is important to know citizens’ perception of different realities. We aimed to determine the factors associated with the perception of inadequate sanitary control in 12 Latin American countries during the COVID-19 pandemic. Methods: This is an analytical cross-sectional study. We asked about six perceptions in regard to different situations experienced by inhabitants of 12 Latin American countries during the pandemic. Frequencies according to country were described and associations versus other important variables were obtained. Results: Out of 8489 participants, 68% stated that there were moments of collective hysteria. Honduras was the country that most perceived inadequate control mechanisms established by the government. Multivariate analysis showed that there were statistically significant differences among many of the countries according to the six evaluated items. The higher the level of education, the greater the perception of poor control in five of the aspects. Additionally, men had a lower perception of inadequate control. The older the age, the lower the perception of inadequate control regarding whether there was collective hysteria and shortages of basic essentials. Those with COVID-19 had a lower perception of medicine shortages. Conclusion: The population of multiple realities in Latin America have perceived a bad management of the pandemic. Our findings may help to improve future similar situations.